Do Work Overtime and Work Overload Hinder the Performance of Mantri at Bank BRI? - Pratomo, Bari Indro; Agustina, Tri Siwi (Indonesian Business Review, 2025)
This study aims to analyze (1) the direct effect of work overload and work overtime on job performance; (2) the direct effect of work overload and work overtime on work-life balance; (3) the direct effect of work overload and work overtime on job performance through work-life balance; (4) the moderating effect of perceived organization support on the effect of work-life balance on job performance. The sampling technique used was a saturated sample (census). The type of research was quantitative causal research, with a sample of 341 clerks working at Bank BRI Regional Office Jakarta 1. Structural equational modeling analysis in this study was conducted using AMOS 20.0 software. The results of the study show that (1) overtime work and work overload do not have a significant direct effect on job performance (2) overtime work and work overload have a negative effect on work-life balance (3) work-life balance fully mediates the effect of overtime work on job performance (job performance) (4) work-life balance was proven to fully mediate the effect of work overload on job performance (5) work-life balance was proven to affect job performance (6) perceived organization support was proven to strengthen the effect of work-life balance on job performance.